German car buyers' willingness to pay to reduce CO2 emissions - Martin Achtnicht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Motorized individual transport strongly contributes to global CO2 emissions, due to its intensive usage of fossil fuels. Current political efforts addressing this issue (i.e. emission performance standards in the EU) are directed towards car manufacturers. This paper focuses on the demand side. It examines whether CO2 emissions per kilometer is a relevant attribute in car choices. Based on a choice experiment among potential car buyers from Germany, a mixed logit specification is estimated. In addition, distributions of willingness-to-pay measures for an abatement of CO2 emissions are obtained. The results suggest that the emissions performance of a car matters substantially, but its consideration varies heavily across the sampled population. In particular, some evidence on gender, age and education effects on climate concerns is provided.
Keywords: C25; D12; Q51; 330; Choice experiment; CO2 emissions; Mixed logit; Passenger cars; Willingness to pay; Personenkraftwagen; Motorisierter Individualverkehr; Verkehrsökologie; Klimaschutz; Willingness to pay; Luftreinhaltung; Deutschland